Strategic human resource management and firm performance : A study of R&D companies in Malaysia - Adnan, Zurina; Abdullah, Hazman Shah; Ahmad, Jasmine; Wan Daud, Wan Din (2010)

(untitled)
This paper examines the effect of Human Resource Management (HRM) practices on performance in the Malaysian R&D industry. Using data from 64 R&D companies, the study found that compensation has positive and direct effect on firm performance while development has negative effect on performance. There is no interaction between the three HRM practices and inter-firm collaboration on performance. The results provide partial support of universalistic approach to strategic HRM.